2004
DOI: 10.1097/01.pas.0000126642.61690.d6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Chromosomal Rearrangements in Subungual (Dupuytren) Exostosis and Bizarre Parosteal Osteochondromatous Proliferation (Nora Lesion)

Abstract: The presence of chromosomal abnormalities in subungual exostosis and BPOP suggests that these lesions are neoplastic, with a different molecular pathogenesis, and that each is a distinct clinicopathologic entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 19 publications
7
33
1
5
Order By: Relevance
“…This is supported by Zambrano et al [26], who identified an abnormal karyotype in one lesion (Ch 12 additional ring chromosomes, Ch 7 trisomy) and nonclonal abnormalities of chromosomes 2, 8, and 14 in another. The finding of a distinct t(1;17)(q32;q21) balanced translocation by Nilsson et al [15] and a t(1;17)(q42;p23) translocation by Endo et al [6] also supports this theory.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…This is supported by Zambrano et al [26], who identified an abnormal karyotype in one lesion (Ch 12 additional ring chromosomes, Ch 7 trisomy) and nonclonal abnormalities of chromosomes 2, 8, and 14 in another. The finding of a distinct t(1;17)(q32;q21) balanced translocation by Nilsson et al [15] and a t(1;17)(q42;p23) translocation by Endo et al [6] also supports this theory.…”
Section: Resultssupporting
confidence: 67%
“…It therefore was suggested by Zambrano et al [26] that BPOP could represent a neoplastic process. Subsequent work by Nilsson et al [15] and Endo et al [6] supports this and suggests t(1;17) represents a distinct translocation point unique to BPOP, thereby excluding the unitary hypothesis.…”
mentioning
confidence: 99%
“…This topic is underrepresented in the orthopaedic literature, because many of the important clinical series have been published in journals from other specialties [4,8,9,12,15,20,21,29,30,33,34,41], reflecting the fact that the condition is treated by many kinds of nonorthopaedic providers. Complete marginal excision of the exostosis appears to mitigate recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This maturation process has been hypothesized to represent a reparative etiology in the response to trauma [11,24,27], despite that the majority of patients described in case reports lack a traumatic history. More recently, some reports have suggested BPOP is a neoplastic process instead of a reparative one [7,12,17,22,26,28].…”
Section: Discussion and Treatmentmentioning
confidence: 99%